Pengenalan Budaya Bengkulu Melalui Puzzle Game Bagi Siswa Sekolah Dasar - Elfianty, Lena; Wahyudi, Jusuf (MEANS (Media Informasi Analisa dan Sistem), 2021)
Teaching aids at the higher education level are not something strange and rare, because the level of need in terms of material presentation is felt more useful and easy. Especially for the basic education level, a tool for delivering material to elementary school children which have been more conventional in the form of teachers reading or writing material, meanwhile, students copy what the class teacher writes. This habit of course will be slow and monotonous and can increase boredom in following the teaching and learning process.Â  To reduce the level of boredom and the less attractive way of delivering this teaching material, it is necessary to have a way that can arouse learning enthusiasm for students at the basic education level, namely in the form of visual displays using computers as the main tool with more material content. new and innovative. This is even more so if it is applied in the form of introduction to nature reserves, history, and cultural heritage.Â  The enthusiasm of the students while trying the puzzle game application based on the introduction of Bengkulu's culture and natural wealth encouraged the students to get to know and understand more about the importance of maintaining and being proud of the natural and cultural wealth of the Bengkulu people.